THE ANALYSIS OF INTERCULTURAL AND PEACE EDUCATION ENGLISH MATERIALS, FOCUSING ON SPEAKING SKILLS IN JUNIOR HIGH SCHOOL - I Komang Agus Tirtayasa, I Komang Agus Tirtayasa; Budiarta, Luh Gd Rahayu; Kusuma, I Putu Indra (Undiksha Press, 2024)
This research aimed to analyze English teaching materials that integrated cross-cultural and peace education, with a focus on speaking skills at the junior high school level. The method used was basic qualitative with document studies to obtain the data. The objects in this research were two books each from three different curricula, namely the 2006 KTSP curriculum, the 2013 curriculum, and the Merdeka curriculum. Two books per curriculum were sufficient to reflect important elements of the research topic, allowing for in-depth analysis without requiring excessive resources and time. The research instruments consisted of an observation sheet, comprehensive notes, and the researcher as the instrument. Data was collected by carrying out thematic analysis, with Inductive Thematic Analysis used to analyze the possibility of themes emerging from the data itself, not determined by pre-existing theories or expectations. The results showed that the 2006 KTSP curriculum provided a strong foundation but required additional interactive elements to deepen cultural understanding and improve speaking skills. The 2013 curriculum offered a more engaging approach but faced challenges in terms of consistency and support. The Independent Curriculum excelled at integrating cultural context and practical application but required effective monitoring and assessment to fully realize its potential. It was concluded that each curriculum had its own advantages and limitations.